2012
DOI: 10.2528/pierb12083108
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effects of Rain Attenuation for an X-Band Satellite System Over Malaysia

Abstract: In this paper, the effect of rain attenuation on the FSS allocation in the 7250-7750 MHz in the Space-to-Earth direction is studied for a satellite at 78.5 • E longitude. A simulation model based on the ITU-R P618-10 rain model is used to predict the rain attenuation in the C-, Ku-and X-bands in 15 different locations with varying rainfall intensities of between 145-300 mm/hr in East and West Malaysia. The simulations assume a 1.8 m receive antenna with 65% aperture efficiency, QPSK modulation and use of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The results in Tables (2,3) showed that phosphorus fertilizer at a concentration of 200 mg P kg -1 soil significantly increased transplant leaves area and sction length as compared with control and 100 mg P kg -1 soil treatments. The obtaind results was in line with those obtaind by [6,8,10,12], and [13]. These results may be due to the function of phosphorus which is presented in all living tissue, however it is concentrated more in the juvenile plant sections.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results in Tables (2,3) showed that phosphorus fertilizer at a concentration of 200 mg P kg -1 soil significantly increased transplant leaves area and sction length as compared with control and 100 mg P kg -1 soil treatments. The obtaind results was in line with those obtaind by [6,8,10,12], and [13]. These results may be due to the function of phosphorus which is presented in all living tissue, however it is concentrated more in the juvenile plant sections.…”
Section: Resultssupporting
confidence: 90%
“…[12] stating that the application on NPK (15:15:15) fertilizer at levels of 1,2,3, and 4 gm transplant -1 of Punica granatum planting in bags containing 23.3 kg of soil significantly increased leaves number, plant height, leaf area with an increase in the fertilizer amount compared to the control. [13] noticed that the application of phosphorus to mustard apple at level of 187 gm plant -1 with the combination of nitrogen and potassium at a level of 388 and 187 gm plant -1 respectively significantly increased plant height, canopy volume, stem girth and leaf area index. At the present time, the fertilization of transplants and various fruit trees with solid and liquid organic fertilizers has increased, including fertilizers that contain amino acids, which are among the nitrogen fertilizers that are characterized by their cheap price, ease of use, low pollution, and their contribution to improving the physical and chemical properties of the soil, which contributes to improve the production and growth of the plants treated with it, and the quantities added depend on soil texture, species and variety of the plant, the prevailing environmental conditions in the region, and other factors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall will bring signal attenuation to the performance of the radio system; meanwhile the scattering effect due to rainfall will cause inter-system interference. Under uniform rainfall conditions, the calculation of clouds and rain attenuation is relatively simple; but in most cases, rainfall is not uniform in time and space, and the unevenness of the cloud/rain medium shows the randomness, which brings great difficulty into the calculation [4]. Therefore, we need to find a precise mathematical model to describe the non-uniformity of the cloud/rain medium, and achieve simulation on clouds and rain fading through establishing a convenient and practical empirical formula.…”
Section: Theoretical Model Of the Darkroom Calibrate-link Methodsmentioning
confidence: 99%